Dermatophytoses: Taxonomy, Pathogenesis, Diagnosis, Resistance, and Management. - Pradeep Singh 1 *; Atul Khajuria1; Ashish Kumar 2 (International Journal of Fungi, 2026)
Dermatophytes, belonging to the family Arthrodermataceae, are keratinophilic fungi responsible for superficial mycoses. Dermatophytoses affect the skin, hair, and nails globally. Over the last few years, dermatophytic infections have seen a sharp rise in India, with the main causative agent being antifungal-resistant Trichophyton mentagrophytes genotype VIII. This review provides a detailed overview of dermatophytoses, including taxonomy, pathogenesis, epidemiology, diagnosis, and treatment. Dermatophytes belong to the kingdom Fungi, family Arthrodermataceae, with seven different species, including Trichophyton, Nannizzia, and Epidermophyton. Dermatophytes cause infection by the adhesion of arthroconidia to keratinized tissues followed by invasion via the production of keratinases. Dermatophytoses present with different manifestations, with the majority being tinea corporis (32.4%), followed by tinea cruris (19.7%), onychomycosis (17.9%), and tinea capitis (13.3%) in the Indian population. Epidemiologically, the infections were previously caused by Trichophyton rubrum, which is now being replaced by antifungal-resistant Trichophyton mentagrophytes, responsible for 64% cases. Factors contributing to the epidemiological shift include the widespread misuse of topical corticosteroids, the prevalence of diabetes mellitus, and the effects of COVID-19. Potassium hydroxide (KOH) microscopy is the diagnostic tool with the highest sensitivity, ranging from 70 to 90%, followed by culture and internal transcribed spacer polymerase chain reaction with 95 to 99% sensitivity. However, the main drawback is the high resistance to terbinafine, with mutations in the squalene epoxidase (SQLE) gene, including Leu393Phe and Ala448Thr mutations, seen in 50 to 65% cases in the Indian population. Terbinafine is the drug of choice, with oral terbinafine being the first-line treatment with cure rates ranging from 70 to 90%, although the widespread resistance to terbinafine is the biggest drawback in the treatment of dermatophytoses. Combination therapy is required to overcome the resistance. Prevention is simple, with emphasis on personal hygiene and avoidance of fomites.
Keywords: Antifungal resistance; Keywords: Dermatophytes; Terbinafine; Trichophyton mentagrophytes; dermatophytosis